PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPAS KELAS IV SD SWASTA HKBP TOMUAN PEMATANGSIANTAR - Simanjuntak, Melvin; Imelda Sabrina Sibarani; Agus Tiara Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Quantum Learning model on the learning outcomes of IPAS (Science and Social Studies) for fourth-grade students at SD Swasta HKBP Tomuan Pematangsiantar. This research used a quantitative research method with a